240 WINDSHIELD SURVEY TO TEACH JUNIOR MEDICAL STUDENTS COMMUNITY HEALTH ASSESSMENT. Issue 1 (1st January 2007) - Feild, C.; Edstrom, P.; Graham, J.; Udouj, J.
Abstract : Introduction: A variety of disciplines use windshield survey (WS), a visual, structured method, as a qualitative measure and teaching tool. The target area can be as small as a neighborhood. Methods: Junior medical students (JMSs) have a 1-week community pediatrics experience with off-campus clinical experiences with underserved and a reflective writing assignment. For 2006-07, a WS of a neighborhood has been added. At the end of the week, JMSs are assigned 4 × 6 block areas in the vicinity of Children's or University Hospital to identify assets and needs in a WebCT format with a locally developed checklist, brief text description, digital photography, and use of Google Earth mapping to identify the area and to identify a solution to an identified need. Results: Twelve surveys were available. Students report 2 to 3 hours to conduct the survey and complete. Students consistently identified poor housing conditions as needs. Assets consistently noted were churches, parks, and public transport. Three students noted presence of neighborhood organizations as assets. Six suggested neighborhood watch. Conclusions: WS is a tool to teach JMSs to identify community health assets and needs, using observation, a basic Internet tool for geographic information system, and digital photography.